Secretions from hypochlorous acid-treated tumor cells delivered in a melittin hydrogel potentiate cancer immunotherapy - Yuhan Zhou; Ting Ye; Chengzhi Ye; Chao Wan; Siyue Yuan; Yushuai Liu; Tianyu Li; Fagang Jiang; Jonathan F. Lovell; Honglin Jin; Jing Chen (Bioactive Materials, 2022)
Autologous tumor cells and cell-derived secretions (CDS) can induce antitumor immune responses. The conditions in which cells are cultured and treated impact CDS, and cellular insults alter their composition and function. In this study, we generated CDS from tumor cells exposed to normal culture conditions, hypoxia, cisplatin, radiotherapy, photodynamic therapy, or hypochlorous acid (HOCl). In vitro HOCl-CDS showed the strongest stimulatory effects on dendritic cells and macrophages compared to CDS generated by hypoxia, cisplatin, radiotherapy or photodynamic therapy. To improve HOCl-CDS activity at the tumor site, we loaded HOCl-CDS into a melittin-encapsulated hydrogel scaffold. When injected intratumorally, the HOCl-CDS hydrogel promoted tumor cell death, cytotoxic T lymphocyte infiltration, and tumor-associated macrophage reprogramming towards an M1 phenotype. The hydrogel inhibited tumor growth and prolonged the survival of mice bearing B16–F10 melanoma. Furthermore, hydrogel-delivered HOCl-CDS augmented the antitumor effects of immune checkpoint blockade. These results underscore the importance of the CDS generation method and delivery approach for improving cancer immunotherapy.